2014
DOI: 10.7763/ijcea.2014.v5.415
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Contamination during Food Preparation, Processing and Handling

Abstract: Abstract-Throughout the world, food processing and handling is a major problem leading to food poisoning and infection. A total of 480 samples was analyzed for Staphylococcus aureus contamination which resulted from food processing. Most of the isolates were taken from food-handlers using nasal swabs. The most contaminated food was chicken pastries, followed by egg sandwiches and spring rolls. Isolates from all samples produced virulence factors hemolysin, coagulase, DNase and enterotoxins. Five different ente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 32 publications
0
15
1
Order By: Relevance
“…Staphylococcus aureus was detected in all hand swab samples (100%) from OFSP puree handlers. This is contrary to findings by Al-Bahry et al [ 37 ] that reported positive results for S. aureus in only 34% of asymptomatic food handlers in their study. From our observation, handling of OFSP in all the stages of processing was done with bare hands and more than 50% of all OFSP puree handlers were not regularly using soap during hand washing despite soap and hand washing instructions being supplied at every hand washing station.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Staphylococcus aureus was detected in all hand swab samples (100%) from OFSP puree handlers. This is contrary to findings by Al-Bahry et al [ 37 ] that reported positive results for S. aureus in only 34% of asymptomatic food handlers in their study. From our observation, handling of OFSP in all the stages of processing was done with bare hands and more than 50% of all OFSP puree handlers were not regularly using soap during hand washing despite soap and hand washing instructions being supplied at every hand washing station.…”
Section: Resultscontrasting
confidence: 99%
“…It is however a challenge destroying heat resistant spores and heat-stable toxins produced by pathogens such as S. aureus in a process involving mild heat treatment of foods. S. aureus counts in foods above 10 5 CFU/g initiate production of heat-stable enterotoxins [ 37 ]. Staphylococcal food poisoning is one of the leading causes of foodborne illnesses worldwide caused by ingestion of food contaminated with preformed S. aureus enterotoxins [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to these authors, the simultaneous production of different types of enterotoxins can increase the toxigenic effect, suggesting that this coproduction may play an important role in mastitis. Enterotoxin A (SEA) is one of the most frequently observed enterotoxins [52], although the literature shows highly variable results in the prevalence of S. aureus enterotoxin genes, depending on the kind of food and the biovar investigated [53]. In the current study, we found 31 (10.8%) isolates encoding the sea gene.…”
Section: Discussionmentioning
confidence: 60%
“…67 Proper hygiene in food handling of food processing equipment ensures limitation of microbial contamination of the product. 68 This aims at improving the keeping quality of the bread.…”
Section: Spoilage and Safety Of Orange-fleshed Sweetpotato Puree Breadmentioning
confidence: 99%